Characterization of biopolymers based antibacterial films enriched with thyme essential oil and their application for milk cake preservation - Mulla, Mehraj Fatema Z.; Ahmed, Jasim; Vahora, Aateka; Pathania, Shivani; Rashed, Mahmoud Said (Frontiers in Food Science and Technology, 2024)
Polysaccharide-based packaging and its ever-increasing applications in response to the need for sustainable and safe packaging have prompted researchers to investigate the development of antimicrobial biopolymer-based packaging for shelf-life enhancement of food samples. A film made by blending chitosan and pectin had good mechanical properties, that is, a tensile strength of 7.43 MPa and an elongation at break of 23.033%. To produce active packaging, thyme essential oil (TEO) was added to the blend at concentrations of 10%, 15%, and 20%. The developed film was characterized for its techno-functional and antimicrobial properties. Further the developed films were employed in an active food packaging system for milk cake. Films with added TEO showed significant enhancements in elongation at break (28.22%) and water vapor barrier properties (30.08 g/h.m2). Additionally, the microstructure of the film was also improved, as demonstrated by scanning electron microscopy (SEM) and atomic force microscopy (AFM) measurements. Fourier transform infrared spectroscopy (FTIR) indicated the interaction of blended matrix (chitosan and pectin) and TEO as observed from the formation of hydrogen bonds with the addition of TEO owing to the OH functional groups. The use of TEO in pectin and chitosan-based film and its application for milk cake packaging showed delayed microbiological contamination and hardness of milk cake samples. The shelf life of milk cake packaged in pectin and chitosan blend film with 20% TEO was enhanced by > 10 days.